2015
DOI: 10.3390/molecules21010029
|View full text |Cite
|
Sign up to set email alerts
|

Mini Review of Phytochemicals and Plant Taxa with Activity as Microbial Biofilm and Quorum Sensing Inhibitors

Abstract: Abstract:Microbial biofilms readily form on many surfaces in nature including plant surfaces. In order to coordinate the formation of these biofilms, microorganisms use a cell-to-cell communication system called quorum sensing (QS). As formation of biofilms on vascular plants may not be advantageous to the hosts, plants have developed inhibitors to interfere with these processes. In this mini review, research papers published on plant-derived molecules that have microbial biofilm or quorum sensing inhibition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 71 publications
(121 reference statements)
2
52
0
3
Order By: Relevance
“…The results indicated that uropathogenic E. coli exopolysaccharide production was inhibited by T. vulgaris using calcoflour dye, and also indicated that thymol and carvacrol (monoterpenes) had a strong inhibitory effect (data not shown) on the uropathogenic E. coli biofilm formation. These results are in agreement with previous results, which demonstrated that thymol and carvacrol are effective against biofilms of Gram-positive and negative bacteria (Ta and Arnason, 2016;Upadhyay et al, 2013). The thymol inhibited the formation of L. monocytogenes biofilms and genes critical to biofilm development were down regulated at concentration of 0.5 mM.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results indicated that uropathogenic E. coli exopolysaccharide production was inhibited by T. vulgaris using calcoflour dye, and also indicated that thymol and carvacrol (monoterpenes) had a strong inhibitory effect (data not shown) on the uropathogenic E. coli biofilm formation. These results are in agreement with previous results, which demonstrated that thymol and carvacrol are effective against biofilms of Gram-positive and negative bacteria (Ta and Arnason, 2016;Upadhyay et al, 2013). The thymol inhibited the formation of L. monocytogenes biofilms and genes critical to biofilm development were down regulated at concentration of 0.5 mM.…”
Section: Discussionsupporting
confidence: 93%
“…Although, the minimum inhibitory concentration of T. vulgaris was calculated as 4 μg mL -1 , to inhibit the E. coli biofilm, a higher concentration was required because the essential oil was esterified. Microbial biofilms organized aggregations of cells attached to a substratum and surrounded by a self-produced extrapolymeric substance (EPS) matrix (Ta and Arnason, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Quorum quenching properties of benzoic acid and derivatives have been also reported against different bacteria species such as E. coli and V. harveyi (Brackman et al, 2009;Ta and Arnason, 2016). In our study, trans 4-(2-carboxy-vinyl) benzoic acid showed higher QS inhibitory potential than the tested extracts (CEs and CFSEs).…”
Section: Discussionsupporting
confidence: 69%
“…In addition, everything seems to indicate that the flavonoid and alkaloidal effects are also related to their ability to interfere with efflux pumps and the mechanism of "quorum sensing" (QS) of undesirable bacteria in the ecosystem, a complex mechanism of action yet to be tested experimentally [34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%